ESENSI KEADILAN DALAM KONTRAK BAKU BERDASARKAN PERSPEKTIF HUKUM HINDU - I Putu Pasek Bagiartha W; Pahrur Rizal (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2022)
The image of a standard contract that puts forward the determination of contract terms unilaterally becomes the core of the study of the essence of justice in a standard contract, especially from the perspective of Hindu law. The method used is a type of qualitative research with a statutory and conceptual approach. For data collection techniques using literature studies and documentation with reference to the analysis of the application of Aristotle's theory of justice to the unilateral application of standard contract terms. Based on the results of the analysis, it was found that the standard contract is included in the category of sources of procedural law (Sadacara) in Hinduism which must not conflict with Sruti and Smerti as lex superiorioir. In the context of Smerti, the standard contract is included in the Arthasastra section, especially the Manawa Dharmasastra group, so the provisions in the Manawa Dharmasastra also apply to standard contracts such as the provisions of Article 1338 of the Civil Code which has similar arrangements with Book VIII Sloka 46 Manawa Dharmasastra, while the provisions of Article 1320 of the Civil Code have essence similarity with Book VIII Manawa Dharmasastra Sloka 143 (regarding object/achievement/guarantee), Sloka 163 (regarding legal competence), Sloka 164 (regarding halal causa), and Sloka 165 (regarding agreement). Furthermore, regarding the essence of standard contract justice, it is categorized as equal justice (justitia commutativa) as long as it fulfills the legal certainty aspect, namely it does not conflict with the provisions of public legislation such as the fulfillment of the provisions of Article 1338 and Article 1320 of the Civil Code, as well as Article 18 Paragraph (1, 2,3,4) Law Number 8 of 1999 concerning Consumer Protection.